2011
DOI: 10.1177/2153368711429305
|View full text |Cite
|
Sign up to set email alerts
|

Violent Victimization of Hispanic College Students

Abstract: This study explores nonfatal violent victimization of Hispanic college students using data from the National Crime Victimization Survey. It compares annual victimization rates characterizing Hispanic students to non-Hispanic students and similarly aged Hispanics not enrolled in college. Results suggest a dramatic decline in student violent victimization rates for Hispanic and non-Hispanic students as well as Hispanics not enrolled in college over the past several years. Differences in the rates of violent vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Among the types of victimization, college students are far more likely to be victimized by property crimes (e.g., personal theft, burglary, and motor vehicle theft) than violent crimes (Bromley, 1992;Fisher, Sloan, Cullen, & Lu, 1998;Fisher & Wilkes, 2003;Fox & Hellman, 1985;Henson & Stone, 1999;Siegel & Raymond, 1992;Sloan, 1992Sloan, , 1994Volkwein, Szelest, & Lizotte, 1995). For both violent and property crimes, however, the risks of victimization for college students in the 18-to-24 age group are significantly lower than for similarly aged nonstudents (Baum & Klaus, 2005;Hart 2003Hart , 2007.…”
Section: The Prevalence and Correlates Of College Student Victimizationmentioning
confidence: 94%
“…Among the types of victimization, college students are far more likely to be victimized by property crimes (e.g., personal theft, burglary, and motor vehicle theft) than violent crimes (Bromley, 1992;Fisher, Sloan, Cullen, & Lu, 1998;Fisher & Wilkes, 2003;Fox & Hellman, 1985;Henson & Stone, 1999;Siegel & Raymond, 1992;Sloan, 1992Sloan, , 1994Volkwein, Szelest, & Lizotte, 1995). For both violent and property crimes, however, the risks of victimization for college students in the 18-to-24 age group are significantly lower than for similarly aged nonstudents (Baum & Klaus, 2005;Hart 2003Hart , 2007.…”
Section: The Prevalence and Correlates Of College Student Victimizationmentioning
confidence: 94%
“…Sloan et al's (1997) study of 3,400 college students and their victimization reporting practices found that more than 75% of crimes identified by these students were not reported to campus police, and included both violent and property crimes in equal measure. Hart's (2003) violent victimization study also found that approximately only 34% of all violent crimes were reported to police, lending statistical support to the findings of later survey studies that suggest that college students, in general, are less inclined to, and therefore, actually report violent and property crimes to the police less than their non-student peers in the general population (Baum & Klaus, 2005). found that campus crime statistics are underreported because they do not take into account all types of crime such as larceny, which tends to have significantly higher incident numbers on college campuses.…”
Section: General Crime Statisticsmentioning
confidence: 68%
“…According to the Campus Crime Statistics website of the U.S. Department of Education, overall levels of crime on campus have been dropping.Compiling the latest aggregate figures available, overall reported crime on campus, including both two-and four-year colleges and universities, has dropped approximately 17% from 2007 to 2009 (Table 1).Even more encouraging, students are at a lower risk from violent and property crime victimization than are their non-student peers in the same age range (18-24) (Hart, 2003(Hart, , 2007. While all types of crime categories captured have declined in total numbers, the rates of criminal activity are still alarmingly high and recent high profile cases, such as the sexual abuse case at Penn State (Pearson, 2013) and the murder of a medical student at the University of Michigan (Jacobs, 2013), have only reinforced the view of many that much more needs to be done to address the problem of crime on campus.While this study is focused on the use of background checks as a mitigating factor in the level of campus criminal activity, we must first understand the overall trends, demographics and contributing factors associated with criminal activity in a www.ccsenet.org/par Public Administration Research Vol.…”
Section: General Crime Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, colleges that screen students for documented criminal histories do not have lower rates of reported crime than those that do (Weissman et al 2010). Rape and sexual assault on college campuses are also predominantly committed by students with no documented criminal records (Hart 2003;Baum and Klaus 2005). In spite of ample evidence that prior criminal conviction is not a strong predictor of law breaking on campus, the focus of campus safety has placed the burden of risk on the heads of students with documented criminal records.…”
Section: Higher Education As a Forgotten Alternative For Reentrymentioning
confidence: 98%